2021
DOI: 10.1016/s2214-109x(21)00318-1
|View full text |Cite
|
Sign up to set email alerts
|

Expanding long-acting contraceptive options: a prospective cohort study of the hormonal intrauterine device, copper intrauterine device, and implants in Nigeria and Zambia

Abstract: Background 30 years after the introduction of the levonorgestrel-releasing intrauterine device in Europe, several sub-Saharan African countries are seeking to broaden access to this contraceptive method. In this study, we aimed to assess 12-month continuation of the hormonal intrauterine device, copper intrauterine device, and implants, as well as to assess women's experiences and satisfaction using these methods in the private sector in Nigeria and the public sector in Zambia. MethodsWe did a prospective coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…International aid funders, such as the Bill & Melinda Gates Foundation, have prioritized and made investments into developing new contraceptive technologies in order to better address women's reproductive needs. Studies have been done in various countries in Sub-Saharan Africa to explore women's openness and opinions about different characteristics of family planning methods (Brunie et al, 2021;Callahan et al, 2019;Callahan et al, 2021;Cartwright et al, 2020). Similar to our study, one study found that duration of use, and familiarity with methods were important attributes of methods in Burkina Faso and Uganda; however, irregular bleeding emerged as a more important attribute to consider than in our study and discreet use was not as prominently discussed (Callahan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…International aid funders, such as the Bill & Melinda Gates Foundation, have prioritized and made investments into developing new contraceptive technologies in order to better address women's reproductive needs. Studies have been done in various countries in Sub-Saharan Africa to explore women's openness and opinions about different characteristics of family planning methods (Brunie et al, 2021;Callahan et al, 2019;Callahan et al, 2021;Cartwright et al, 2020). Similar to our study, one study found that duration of use, and familiarity with methods were important attributes of methods in Burkina Faso and Uganda; however, irregular bleeding emerged as a more important attribute to consider than in our study and discreet use was not as prominently discussed (Callahan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a prospective cohort study of long-acting reversible contraceptive users at the 21 SFH-supported public health facilities to measure method-specific continuation rates and assess women’s satisfaction and experiences with LARCs [ 25 ]. The present paper draws on the baseline survey with women ages 16–49 who received the hormonal IUD, copper IUD, implant (any type) or three-month injectable from one of the facilities during the recruitment period and follow-up in-depth interviews (IDIs) with a subset of women.…”
Section: Methodsmentioning
confidence: 99%
“…CIMCs can also have advantages that motivate individuals to begin and/or continue contraceptive use. Reduced menstrual bleeding, pain, or cramping, as well as paused bleeding can offer increased freedom to engage in regular activities, improved convenience, improved sexual satisfaction, decreased stress and worry, and reduced spending if fewer menstrual materials are needed 2 , 17 . Some individuals choose to use contraception primarily, or at least in part, for the resulting beneficial menstrual changes, including the management of menstrual and gynecologic disorders and symptoms, such as heavy menstrual bleeding, which affects approximately 30 percent of those who menstruate 18 , and endometriosis, which affects an estimated 10% of menstruators worldwide 19 .…”
Section: Contraceptive-induced Menstrual Changesmentioning
confidence: 99%